UPAYA GURU AL-QUR’AN HADITS DALAM MENGATASI KESULITAN BELAJAR MEMBACA AL-QUR’AN PADA KELAS VIII MTS AL-IKHLAS MOWEWE”. - Hasania, sitti; Zakariah, Muhammad Askari (Jurnal Teknologi Pendidikan Madrasah, 2020)
The background of this research is that the culture of reading Al-Qur'an in homes after fardhu prayer is rarely heard. Children who had memorized their Koran when they were in elementary school, now no longer repeat their recitation of the Quran. Reading the Koran has now been replaced by readings or other information media such as: Articles, Facebook, YouTube, newspapers or newspapers, magazines, television and others, even though they know reading the Qur'an is worship that is rewarded by Allah SWT. In this case, the teaching and learning process is very important to improve the quality of children in reading the Al-Qur'an, and in the learning process the efforts or efforts of the teacher are very important for the continuity of a good teaching and learning process. This research aims to explain the efforts of the Al Qur'a n Hadith teacher in overcoming difficulties in learning to read the Al-Qur'an. This study uses a qualitative approach, with observation data collection techniques, interviews and documentation. As for analyzing the data using descriptive qualitative data analysis. This study concludes that: There are four causes of difficulties for students in learning the Qur'an at school, namely individual causes (less intensity of time to read Al-Qur'an due to laziness of students), difficulty in distinguishing the sound of letters that are sociable. long or short, difficulties in knowing the signs of stopping the letters of the Qur'an, and difficulties in understanding the law of reading recitation. This cannot be separated from the lack of parental control over their children when they are at home, the limited knowledge of teachers in the TPQ areas where students live, and the limited school facilities and infrastructure that are able to support student learning outcomes, especially in the subject of Qur’an Hadits.